Fibro Osseous Lesions of The Craniofacial Structures – A Clinical Study (Update Dental College Journal, 2018)
Fibro osseous lesions area diverse group of disorders characterized by replacement of normal archi- tecture of bone by a benign connective tissue matrix that displays various amount ofmineralizationin the form of woven bone or cementum. It includes developmental, reactive and neoplastic lesions.  The different type of fibro-osseous lesions express a common clinical and radiological features. Soad- equate knowledge and clinical observationare necessary for proper interpretation and appropriate diagnosis of these lesions.becausemanagement of patients with fibro-osseous lesions are case specificandindividualized.The aim of this study was to analyse the clinical, radiological and histo- pathological characteristics of fibro osseous lesions andprovide a proper management system affect- ed by this type of lesions. Materials and methods:The retrospective study was performed in the Department of Oral & Maxillofacial surgery, Dhaka Dental College and Hospital, Dhaka, Bangladesh from a period of January 2015 to January 2018. Patients were selected for this study based on clinical, radiological and histopathological confirmation of fibro-osseous lesion. The management of each case were plannedand follow-up data were also documented. Results: A total number of 30 patients were selected for this study.The most common fibro-osseous lesionsin this study were fibrous dyspla- sia 10 (33%) and ossifying fibroma 20 (67%).The mean age offibrous dysplasia were 17.4 years with an age range 12 to 33 years and at ossifying fibroma the mean age were 30.35 years with an age range 12 to 57 years. Female17 (57%) represented the majority of the affected patients. Fibrous dysplasia were more common in maxilla(70%) and ossifying fibroma were more common in the man- dible(60%).Surgical recontouring and clinical observation were treatment of choice infibrous dysplasia and surgical resection, enucleation and curettage were treatment of choice in ossifying fibroma. Conclusion:The most common fibro-osseous lesion in our clinical study was fibrous dysplasia and ossifying fibroma which presents painless bony swelling and deformity in maxilla and mandible. Fibrous dysplasia presents as a homogenous, radioopacity,ill defined border and ossifying fibroma presents a mixed radioopacity and radiolucent lesion that is well demarcated from normal bone. Surgi- cal recontouring and clinical observation was done in treatment of fibrous dysplasiaand ossifying fibroma wastreated enucleation and curettage, segmental resection completelyenucleatefromsur- rounding bone.Update Dent. Coll. j: 2018; 8 (1): 45-54